Describing Modularity in the Forewings of the Mango Leafhopper (Idioscopus clypealis) - Manseguiao, Mark Ronald S.; Bonachita, Elbridge D.; Adamat, Liza A.; Demayo, Cesar G. (Journal of Informatics and Mathematical Sciences, 2017)
The effects of environmental factors on genetic modules is important in understanding the development of organisms. This study was conducted to determine the developmental modules in the forewings of the mango leafhopper (Idioscopusclypealis) and establish if variation exists between populations attacking different hosts and between sexes. A total of 199 landmarks points were used to outline the margins and wing venation of the leafhopper. Models were constructed to hypothesize modularity in the wings. The É£* (Gamma*) test for Goodness of fit (GoF) was used to assess the best fit model. Results showed that the forewings of I. clypealis is partitioned into 5 developmental modules bounded by the major veins in all populations except for the left forewing of the female leafhopper in Paho variety (É£*= -0.25572, P=1). The results suggest that wing development is conserved but may be affected by host.